(x+2)³=x³+8
x³+3*x²*2+3*x*2²+2³=x³+8
x³+6x²+12x+8=x³+8
6x²+12x=0
6x(x+2)=0
x=0 или x+2=0
x=-2
ответ: -2; 0
(3x-1)³=27x³-1
(3x)³-3*(3x)²*1+3*3x*1²-1³=27x³-1
27x³-27x²+9x-1=27x³-1
-27x²+9x=0
-9x(3x-1)=0
x=0 или 3x-1=0
3x=1
x=1/3
ответ: 1/3; 0
*** Для решения применялись формулы куба суммы и куба разности:
(a+b)³=a³+3a²b+3ab²+b³
(a-b)³=a³-3a²b+3ab²-b³
(x+2)³=x³+8
x³+3*x²*2+3*x*2²+2³=x³+8
x³+6x²+12x+8=x³+8
6x²+12x=0
6x(x+2)=0
x=0 или x+2=0
x=-2
ответ: -2; 0
(3x-1)³=27x³-1
(3x)³-3*(3x)²*1+3*3x*1²-1³=27x³-1
27x³-27x²+9x-1=27x³-1
-27x²+9x=0
-9x(3x-1)=0
x=0 или 3x-1=0
3x=1
x=1/3
ответ: 1/3; 0
*** Для решения применялись формулы куба суммы и куба разности:
(a+b)³=a³+3a²b+3ab²+b³
(a-b)³=a³-3a²b+3ab²-b³